Needs for conservation for Fish variety of the River Choto Jamuna, Bangladesh - Xafr, Monjurul; Arafat, Chakra; Farzana, Saminul (Advances in Aquaculture and Fisheries Management, 2013)
River Choto Jamuna is an important and well-known river in north-west Bangladesh in terms of fish production and source of income for many fishermen living beside where this study has been conducted from January to December, 2012. This study revealed the existing fish species and their composition along with diversity, richness and evenness indices. A total of 63 species of fishes have been recorded belonging to 41 genera, 23 families and 9 orders. Cypriniformes was recorded as the most diversified fish group in terms of both number of species and individuals observed. Of all the fishes found, 41.27% species were threatened in Bangladesh including 15.87% vulnerable, 15.87% endangered and 9.52% critically endangered species. Overall values of diversity, richness and evenness indices were found to be 3.717, 6.954 and 0.897, respectively. Finally, considering all the findings, the establishment of fish sanctuaries to conserve available fish species, both threatened and non-threatened, naturally is recommended.